The impact of age and forestry practices on the wood quality of Pinus taeda L. grown in different sites in Southern Brazil - Neto, Thayanne Caroline Castor; dos Santos, Vaniele Bento; Kulmann, Matheus Severo de Souza; Cirilo, Nauan Ribeiro Marques; Schumacher, Mauro Valdir; Stape, José Luiz [UNESP]; Vidaurre, Graziela Baptista (Elsevier, 2024)
Forest yield is significantly influenced by silvicultural practices. Moreover, environmental conditions play key role in trees’ growth and wood features. Accordingly, the aim of the current study is to explore the effects of age, location, fertilization and thinning on the wood quality of Pinus taeda trees grown in different sites in Southern Brazil. Trees collected in seven municipalities in Southern Brazil were used to assess age impact on wood quality. Trees collected in three municipalities (Jaguariaíva and Ponta Grossa in Paraná State, and Rio Negrinho in Santa Catarina State) were assessed to analyze forestry practices. Collected trees were subjected to four different treatments: PS (No thinning and no fertilization), PF (No thinning and fertilization), US (Thinning and no fertilization), and UF (Thinning and fertilization). Age had significant impact on Pinus taeda wood's basic density; younger trees presented lower density. In addition, the adopted forestry methods did not affect this species’ basic wood density. Non-fertilized trees presented higher density than the fertilized ones. Trees grown in different locations in Jaguariaíva County recorded the highest wood density. Water shortage was identified as the main climatic factor influencing wood density.
Keywords: Loblolly pine; Silvicultural treatments; Wood density